2018
DOI: 10.4187/respcare.06353
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Pulmonary Rehabilitation in Improving Quality of Life for Subjects With COPD

Abstract: BACKGROUND: Increasingly, studies have shown that application of pulmonary rehabilitation (PR) may improve the quality of life (QOL) of patients with COPD. However, some studies remain controversial and were limited to small number of participants. We designed a systematic review and meta-analysis to evaluate the efficacy of PR in improving the QOL for subjects with COPD. METHODS: We searched the Cochrane Library, PubMed, EMBASE, and Web of Science up to March 29, 2018, to identify relevant randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…In contrast, intriguing results were reported in terms of the number of respiratory events and hospitalization rate, with two studies suggesting positive effects of tele-monitoring systems on these crucial outcomes [ 38 , 39 ]. Thus, these results are particularly important due to the higher rate of pulmonary complications in frail older patients that might need a comprehensive approach, including digital innovation, with positive implications in terms of both clinical outcomes and sanitary cost reduction [ 41 45 ]. In addition, it should be noted that positive effects on sanitary costs have been previously reported, underlining that the clinical implementation of a tele-monitoring system in routine clinical settings might be a suitable strategy to enhance the long-term health care of older patients affected by COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, intriguing results were reported in terms of the number of respiratory events and hospitalization rate, with two studies suggesting positive effects of tele-monitoring systems on these crucial outcomes [ 38 , 39 ]. Thus, these results are particularly important due to the higher rate of pulmonary complications in frail older patients that might need a comprehensive approach, including digital innovation, with positive implications in terms of both clinical outcomes and sanitary cost reduction [ 41 45 ]. In addition, it should be noted that positive effects on sanitary costs have been previously reported, underlining that the clinical implementation of a tele-monitoring system in routine clinical settings might be a suitable strategy to enhance the long-term health care of older patients affected by COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Early initiation of PR can potentially minimize the effect of acute exacerbations on the skeletal muscle and prevent the deterioration of skeletal muscle to a significant extent [23], thus appearing to be an effective strategy to change the course of the disease [24]. Several other studies have demonstrated significant improvement in muscle function and quality of life [25][26][27][28][29][30], psychosocial wellbeing [31], reduction in mortality, and rate of hospitalization [32] following successful completion of PR. The benefits of PR can be further maximized by introducing supplemental nutrition [33,34].…”
Section: Pulmonary Rehabilitation: the Pressing Priority In The Management Of Copdmentioning
confidence: 99%
“…Although chronic diseases and frailty are often treated as separated conditions, they share different multilevel interactions, and several disabling conditions play a pivotal role in frailty onset [ 11 ]. Due to the higher rate of pulmonary complications, frail patients might require an integrated rehabilitation approach including PR with relevant implications in terms of both physical wellbeing and quality of life improvement [ 12 , 13 , 14 , 15 , 16 ]. However, to the best of our knowledge, no previous study emphasized the role of PR in these patients.…”
Section: Introductionmentioning
confidence: 99%